The Relationship Between Smartphone Use and Eye Fatigue - Ratika Febriani; Indriyani Indriyani; Rury Tiara Oktariza; Putri Zalika Laila Mardiah Kesuma; Fahmi Bahar Wasri; Riska Ayu Wulandari (MESINA (Medical Scientific Journal), 2026)
ABSTRACTEye strain (asthenopia) is a common complaint resulting from the increasing use of digital devices. Data from the World Health Organization (WHO) indicate that the global prevalence of asthenopia ranges from 75% to 90%. The growing use of smartphones, particularly among university students, has the potential to increase the risk of this condition. This study aims to analyze the relationship between smartphone usage characteristics—namely viewing distance, duration of use, and usage position—and the occurrence of eye strain among students. This research employed an analytical observational design with a cross-sectional approach. The sample consisted of 209 students selected through proportionate stratified random sampling. Data were collected using a smartphone usage questionnaire and the Visual Fatigue Index (VFI), and subsequently analyzed using the chi-square test with a 95% confidence level. The results showed that 78% of respondents experienced eye strain. There was a significant relationship between viewing distance (p=0.001), duration of use (p=0.001), and smartphone usage position (p=0.001) and the incidence of eye strain. In conclusion, ergonomic factors related to smartphone use play an important role in the development of eye strain. Education on proper device usage is necessary to minimize the risk of eye health problems.Keywords: distance, duration, smartphone, eye strain